2017
DOI: 10.18632/oncotarget.16963
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and the risk of biliary tract cancer: a systematic review and dose-response meta-analysis of observational studies

Abstract: Recent studies have shown that tea consumption is associated with the reduced incidence of some types of cancer, possibly including biliary tract cancer. However, the epidemiological evidences for the association with risk of biliary tract cancer are contradictory. Thus, we performed meta-analysis of published observational studies to assess the association between tea consumption and risk of biliary tract cancer. Relevant studies were identified by searching PubMed, EMBASE, and ISI Web of Science published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…One of the most prominent associations identified in the current umbrella review was that between tea consumption and diverse cancers; beneficial associations of tea consumption with gastric cancer, oral cancer, lung cancer, biliary tract cancer, thyroid cancer, ovarian cancer, leukemia, and glioma, and of green tea consumption with esophageal cancer and endometrial cancer we observed, although most of these had substantial heterogeneity that might not be readily explained by the epidemiological design, sex, or other important determinants for decreasing the risk of developing cancer. Interestingly, in most cohort and case‐control studies, cancer risk reduction was more frequently observed with green tea consumption.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One of the most prominent associations identified in the current umbrella review was that between tea consumption and diverse cancers; beneficial associations of tea consumption with gastric cancer, oral cancer, lung cancer, biliary tract cancer, thyroid cancer, ovarian cancer, leukemia, and glioma, and of green tea consumption with esophageal cancer and endometrial cancer we observed, although most of these had substantial heterogeneity that might not be readily explained by the epidemiological design, sex, or other important determinants for decreasing the risk of developing cancer. Interestingly, in most cohort and case‐control studies, cancer risk reduction was more frequently observed with green tea consumption.…”
Section: Discussionmentioning
confidence: 83%
“…In separate meta‐analyses, high consumption of tea was related to a reduced risk of biliary tract cancer, oral cancer, leukemia, thyroid cancer, lung cancer, and glioma . Considering the different types of tea, high consumption of green tea was associated with a reduced risk of liver cancer, ovarian cancer, endometrial cancer and esophageal cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Definite heterogeneity was assumed if the p value was less than 0.1. Sensitivity analyses were conducted by altering the pooling model [21]. In addition, a sensitivity analysis was carried out to evaluate the influence of each individual study on the summarized estimate by means of successively excluding one research study at a time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the stability of the outcomes was assessed by sensitivity analysis via sequential omission of one by one, which was conducted by altering the pooling model (fixed-effects model or random-effects model) and eliminating researches with NOS sources under 7 as well. 26 …”
Section: Methodsmentioning
confidence: 99%